Ungoverned Spaces and the Challenges of Counterterrorism in West Africa Sub-Region - Chilaka, Francis Chigozie; Doutimi, Yonmo; Chigozie, Joy Nwakaego (Journal of Contemporary International Relations and Diplomacy, 2024)
In recent times, terrorist groups; Islamic fundamentalists; separatist agitators; armed bandits and other criminal elements have begun harnessing the availability of ungoverned spaces in West African States. From such locations, they launch their horrific acts of terror aimed at destabilizing the corporate existence of these states and the overall peace and security of the sub-region. Porosity of border security, poverty and ungoverned spaces are linked as stimulants to terrorism in the West African sub-region. It is against this backdrop that this paper examined the issues and challenges of terrorism and counterterrorism in West Africa. The paper is anchored on the fragile state theory, which argues that terrorism oozing from ungoverned spaces and porosity of borders have adverse effects on the security of the region. The study relied essentially on secondary sources of documentary evidence through thorough literature review. Findings revealed that the region became volatile and easily susceptible to terrorist activities because the ungoverned spaces provided them unhindered operational bases. Therefore, the paper concluded and recommended that West African States should build a synergic security architecture in the form of independent inter-region police force recruited from member countries, and deployed to transnational borders to carry out routine border patrol in collaboration with national customs and immigration personnel. Sequel to aforementioned recommendation, governments of West African States, in collaboration with their National Security Advisers, are to provide intelligence information and report to the region’s inter-region police to enhance their security duties and ensure peace and orderliness in the sub-region.